Introducing Clinical Pathology Course to Fourth Year Medical Students as a Bridge between Pre-clinical and Clinical Medical Sciences - Upadhyaya Kafle, S.; Singh, M.; Kafle, N.; Sinha, A.; Guragain, P.; Rimal, H. S. (Kathmandu University Medical Journal, 2022)
There isn’t any vertical integration of pre-clinical and clinical sciences subjects in the existing Kathmandu University MBBS curriculum. Many of the graduates are not able to correlate the clinico-pathological aspects of various diseases as a result the rational use of investigations for diagnosing various diseases is compromised. There are few published examples of implementation of pathology instruction courses during the clinical years of medical training but it is not universally practiced. This lack of exposure to pathology may lead to poor understanding of laboratory testing and the role of pathologists in patient care. To set and implement an exemplary vertical integration of pre-clinical science with clinical science. A 12 credit hours clinical pathology education course comprising clinical hematology, cytopathology and histopathology was developed. Students belonging from the ongoing fourth year MBBS course of Birat Medical College were enrolled in the course. All of the interactive lecture sessions were delivered via an e-learning interface, using the Zoom platform as the main teaching methods. Evaluation of students’ achievement of learning objectives was conducted through distributing pre and post-test online multiple-choice questionnaires. Chi-square tests were used to compare the variables between pre-test and post-test questionnaire responses. Results suggested that the designed clinical pathology course is valuable. The pretest and post-test questionnaire responses revealed the positive impact regarding the importance of introducing clinical pathology courses within the clinical year of MBBS undergraduate curriculum. Response rate to the online session was 100%. The point of agreement between the pre-test and post-test questionnaire responses were highly achieved after intervention of the clinical pathology course. A statistically significant result (p < 0.05) between all of the pre-test and post-test questionnaire responses was noted. There was a strong positive recommendation for incorporating clinical laboratory medicine courses within the MBBS clinical science curriculum. The improvement observed among fourth-year MBBS students on learning the importance of clinical pathology courses was encouraging. This experience thus contributed to set and implement an exemplary vertical integration of pre-clinical science with clinical science.